REFORMASI PANTEKOSTAL SEBAGAI PEREMAJAAN KEKRISTENAN PALING RADIKAL SEJAK PEMBARUAN JOHN CALVIN - John Mansford Prior (Jurnal Ledalero, 2016)
The Pentecostal Churches and Charismatic movements within the mainstream Churches are by far the fastest growing sectors of Christianity. In particular, migrants are attracted from their mainstream ecclesial roots to a myriad of Pentecostal communities in urban settings, to congregations that are small and welcoming, but also to the mega-Churches. This essay looks at key characteristics of urban migrants and the significant elements of the Pentecostal/charismatic communities that attract them as new members. Particular attention is given both to the evolving political dimension of these communities and to the “gender paradox” whereby women are more likely to join Pentecostal/Charismatic Churches where they discover a renewed dignity and identity while these very Churches are largely governed by men. Examples are given as diverse as that among Protestant urban migrants in mainland China, and Catholic domestic and international migrants within and from the Philippines. The essay concludes with an analysis that looks at the data as a reflection of modernity and its consequent challenge to mainstream Churches that have as yet failed to adapt. Keywords: Pentecostal Church, Charismatic Movement, the immigrants,Chinese immigrants, migrant Filipino, gender paradox of modernity ------------------------------------------------------------------------------------------------------------------------ Gereja-gereja Pantekostal, juga gerakan Karismatik dalam Gereja-Gereja arus utama, merupakan sektor kekristenan yang sedang bertumbuh secara paling pesat. Secara khusus, para migran yang tercabut dari akarnya dalam Gereja mereka di tempat asal, mengarah ke komunitas-komunitas Pantekostal di daerahdaerah perkotaan, baik dalam jemaat-jemaat kecil, maupun dalam Gereja-Gereja mega. Esai ini memperlihatkan ciri-ciri kunci dari migran perkotaan dan unsur-unsur yang signifikan dari kalangan Pantakostal/ Karismatik yang menarik mereka sebagai anggota baru. Perhatian khusus diberikan kepada dimensi politik yang berkembang dan pada “paradoks gender” di mana perempuan lebih mungkin bergabung dalam Gereja Pantekostal/gerakan Karismatik, di mana mereka menemukan martabat dan jatidiri baru. Walau demikian, sebagian besar Gereja Pantekostal masih diatur oleh kaum lelaki. Beragam contoh ditampilkan, seperti yang terjadi di kalangan migran perkotaan Protestan di Cina daratan, dan juga di kalangan migran domestik dan internasional Katolik dari Filipina. Esai ini diakhiri dengan analisis yang memperlihatkan data yang mencerminkan modernitas, dan karena itu tantangan bagi GerejaGereja arus utama yang sampai kini gagal menghadapnya. Kata-kata kunci: Gereja Pentakostal, Gerakan Karismatik, kaum perantau, perantau Cina, migran Filipina, gender paradoks, modernitas